Multicenter study on the consciousness‐regaining effect of a newly developed artificial liver support system in acute liver failure: An on‐line continuous hemodiafiltration system. Issue 2 (17th November 2020) - Takikawa, Yasuhiro; Kakisaka, Keisuke; Suzuki, Yuji; Ido, Akio; Shimamura, Tsuyoshi; Nishida, Osamu; Oda, Shigeto; Shimosegawa, Tooru
Abstract : Aim: Acute liver failure (ALF) patients with coma need to be revived not only for spontaneous recovery but also as a bridge to liver transplantation. We developed a new high‐volume plasma purification system using an on‐line continuous hemodiafiltration (CHDF) system, and evaluated its safety and efficacy in a multicenter study. Methods: A single arm interventional study using the new apparatus was undertaken in the six major liver centers in Japan. The primary end‐point was the proportion of patients who regained consciousness within 10 days, which was compared with a historical control (47%). Nine ALF patients were enrolled and treated with the new machine. One patient was excluded because of the need for artificial respiration support according to the established protocol. Results: Seven of eight (87.5%) patients regained consciousness during the on‐line CHDF session, with five of those seven waking within 4 days. After waking, one patient spontaneously recovered, three received liver transplantation, two died of liver failure, and one died of another disease. The plasma ammonia levels significantly decreased after the start of on‐line CHDF from 182.5 ± 64.8 μg/dL (mean ± SD) on day 0 to 87.0 ± 38.9 μg/dL on the last day of the session ( P < 0.001). Similarly, the plasma glutamine level also significantly decreased from 2069 ± 1234 μmol/L to 628 ± 193 μmol/L. Although seven severe adverse events occurred during on‐line‐CHDF, no causal relationship with liver support was recognized. Conclusions: The newly developed on‐line CHDF system showed high efficacy for regain of consciousness and excellent therapeutic safety for managing ALF.